Preliminary results of minimally invasive stereotaxic surgery of intraparenchymal hematomas at the Hospital of Mali (23 cases) - Mahamadou Dama; Oumar Diallo; Oumar Coulibaly; Daouda Sissoko; Theodore Maxim Coulibaly; Kalba Tembine; Thomas Coulibaly; Fengqiang Liu; Cisse El Hassimi Mohamed; Drissa Kanikomo (Romanian Neurosurgery, 2023)
Introduction: Spontaneous intracerebral haemorrhage (ICH) is a rupture of blood vessels in the brain parenchyma, in the absence of any underlying structural vascular lesion. It’s destructive and associated with a high mortality rate. There is a specific threshold of hematoma evacuation to impact mortality or functional outcome in ICH even the curative effect of minimally invasive hematoma removal for cerebral haemorrhage has not been fully recognized worldwide. We aim to evaluate surgical performance on hematoma volume and functional outcomes of patients.